2006
DOI: 10.1590/s0034-72992006000600005
|View full text |Cite
|
Sign up to set email alerts
|

Qualidade de vida em crianças com distúrbios obstrutivos do sono: avaliação pelo OSA-18

Abstract: Distúrbios obstrutivos do sono (DOS) são prevalentes e existem evidências de afetarem a qualidade de vida das crianças. OBJETIVO: Avaliar a qualidade de vida de crianças com DOS antes e após adenoidectomia ou adenotonsilectomia. MATERIAL E MÉTODOS: Estudo prospectivo de intervenção, tipo antes e após, com componente avaliativo. Foi recrutada uma amostra consecutiva de crianças com indicação de adenoidectomia ou adenotonsilectomia em um ambulatório de otorrinolaringologia e aplicado aos cuidadores um questionár… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 31 publications
1
5
0
1
Order By: Relevance
“…The results comparing preoperative and early postoperative data (about 30 days after surgery) have been published by Silva et al, 27 and are summarized below.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The results comparing preoperative and early postoperative data (about 30 days after surgery) have been published by Silva et al, 27 and are summarized below.…”
Section: Resultsmentioning
confidence: 99%
“…The OSA18 questionnaire, developed by Franco Jr. et al 20 and adapted into Portuguese language by Silva et al, 27 was applied in three moments to the caretakers of children included in this study to assess the qualify of life of these patients. In the first of these moments -a preoperative visit about 30 days before surgery -a baseline score was obtained as a parameter for assessing the quality of life of children before adenoidectomy or adenotonsillectomy.…”
Section: Series and Methodsmentioning
confidence: 99%
“…Regarding the quality of life protocols that aimed at analyzing the impact of respiratory problems, exist the OSA-18 and Pittsburg, focused on the OSA (SILVA; LEITE, 2006;BERTOLAZI, 2008), the PAQLQ-A, for subjects with asthma (LA SCALA; NASPITZ; SOLÉ, 2005) and the Protocol advocated by Ribeiro (2006), which is the only one that evaluates the mouth breather, without distinction of condition, but still unused by the scientific literature.…”
Section: Discussionmentioning
confidence: 99%
“…The quality of life showed no correlation with the ESS; however, the study of Silva and Leite found a negative impact on the quality of life of SDB and found an association between SDB and worse quality of life in children with obstructive sleep disorders. 40 …”
Section: Discussionmentioning
confidence: 99%